2017
DOI: 10.3389/fnhum.2017.00379
|View full text |Cite
|
Sign up to set email alerts
|

Bodily Sensory Inputs and Anomalous Bodily Experiences in Complex Regional Pain Syndrome: Evaluation of the Potential Effects of Sound Feedback

Abstract: Neuroscientific studies have shown that human's mental body representations are not fixed but are constantly updated through sensory feedback, including sound feedback. This suggests potential new therapeutic sensory approaches for patients experiencing body-perception disturbances (BPD). BPD can occur in association with chronic pain, for example in Complex Regional Pain Syndrome (CRPS). BPD often impacts on emotional, social, and motor functioning. Here we present the results from a proof-of-principle pilot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 80 publications
2
36
0
Order By: Relevance
“…As revealed by previous research, auditory feedback can alter body perception in healthy controls, 15,16,[35][36][37] as well as in clinical populations. 22,23,[34][35][36][37] In this proof-of-principle pilot study, our main aim was to assess the possibility of modifying dysfunctional gait asymmetry patterns in chronic stroke patients with lower limb hemiparesis by providing manipulated auditory feedback of their walking sounds. While there are a number of applications for movement rehabilitation using sound with information about the actual body position or movement, our study is novel in that it shows the potential of using sound in gait rehabilitation by means of the introduction of changes in body perception in chronic stroke patients.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…As revealed by previous research, auditory feedback can alter body perception in healthy controls, 15,16,[35][36][37] as well as in clinical populations. 22,23,[34][35][36][37] In this proof-of-principle pilot study, our main aim was to assess the possibility of modifying dysfunctional gait asymmetry patterns in chronic stroke patients with lower limb hemiparesis by providing manipulated auditory feedback of their walking sounds. While there are a number of applications for movement rehabilitation using sound with information about the actual body position or movement, our study is novel in that it shows the potential of using sound in gait rehabilitation by means of the introduction of changes in body perception in chronic stroke patients.…”
Section: Discussionmentioning
confidence: 95%
“…Participants were asked to wear a system, which will be referred to as "sonic shoes," previously described in detail in Tajadura-Jiménez et al [35][36][37] that allows the dynamic modification of footstep sounds while walking and measures behavioral changes. As shown in Figure 1A, the system is composed of a pair of strap sandals with hard rubber soles.…”
Section: Apparatus and Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…[9,32,34,51,81]) we found that participants with CRPS had distorted representations of their affected limbs. Tajadura-Jiménez and her colleagues recently showed that people with CRPS are able to update their bodily representations, because manipulating the frequency of auditory feedback during walking changed the perceived dimensions of the CRPS-affected limb [75]. However, they did not directly compare the performance of the people with CRPS to controls, meaning it is unclear from their results if the extent of this updating was normal.…”
Section: Discussionmentioning
confidence: 99%
“…Brun et al [44], N = 13; Bultitude et al [45], N = 24; Kotiuk et al [46], N = 50; Lewis and Schweinhardt [47], N = 22, HC; Tajadura-Jiménez et al [48], N = 12…”
Section: Behavioural Neurologymentioning
confidence: 99%